Hydrophobic, solid acid catalysts for production of biofuels and lubricants - Sreeprasanth, Pulinthanathu Sree; Srivastava, R.; Srinivas, D.; Ratnasamy, P. (Applied Catalysis A-General, 2006)
A novel application of Fe-Zn double-metal cyanide (DMC) complexes as solid catalysts in the preparation of fatty acid alkyl esters (biodiesel/biolubricants) from vegetable oils is reported. The catalysts are hydrophobic (no H2O adsorption at reaction temperatures) and contain only Lewis acidic sites (NH3 and pyridine adsorption). Bronsted acid sites are absent (absence of 1546 and 1639 cm(-1) bands on adsorption of pyridine). Basic sites are also absent (no CO2 adsorption). Unlike the homogeneous or other solid catalysts (like ZnO-Al2O3, for example), the Fe-Zn, DMC catalysts are highly active even for the simultaneous transesterification of triglycerides and esterification of the free fatty acids (FFA) present in unrefined and waste cooking oils as well as non-edible oils. They are also tolerant of water, probably, due to their surface hydrophobicity. A relationship between the transesterification activity and the concentration of strong Lewis acid sites has been observed. Coordinatively unsaturated Zn2+ ions in the structure of the Fe-Zn complex are the probable active sites. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: alcoholysis of vegetable oils; Biodiesel; Biolubricants; double-metal cyanides (DMC); esterification of free fatty acids; fatty acid alkyl esters; fatty acid methyl esters; solid Fe-Zn catalysts; transesterification of vegetable oils

Hydrolysis of vegetable oils and fats to fatty acids over solid acid catalysts - Satyarthi, J. K.; Srinivas, D.; Ratnasamy, P. (Applied Catalysis A-General, 2011)
Solid Fe-Zn double-metal cyanide (DMC) complexes exhibit high catalytic activity for hydrolysis of edible and non-edible vegetable oils and animal fat. In a batch reaction, complete conversion of vegetable oil triglycerides to fatty acids with selectivity greater than 73 wt% was obtained at temperatures as low as 463 K, autogenous pressure and with 5 wt% of catalyst. Catalytic activity of DMC was superior to Amberlyst (TM) 70, SAPO-11, H-beta, HY, MoO(x)/Al(2)O(3) and sulfated zirconia. Rates of hydrolysis were greatly enhanced when solvents (tetrahydrofuran or N,N-dimethylformamide), phase transfer agents (tetrapropyl ammonium bromide) and products (a mixture of mono-/diglycerides and fatty acids) or fatty acid was added to the feed. Surface hydrophobicity which enables high wettability and activation of glycerides on active, acidic sites of reusable DMC is attributed to be the major cause for its superior catalytic activity. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Double-metal cyanide complex; Fat splitting; Fatty acids; Hydrolysis of vegetable oils and fats; solid acid catalyst